1990
DOI: 10.2172/10185415
|View full text |Cite
|
Sign up to set email alerts
|

Development and process evaluation of improved Fischer-Tropsch slurry catalysts. Final report

Abstract: DISCLAIMER Portions of this document may be illegible in electronic image products. Images are produced from the best available original document. DISCLAIMER This report was prepared as an account of work sponsored by the United States Government. Neither the United States nor the United States Department of Energy, nor any of their employees, makes any warranty, expressed or implied, or assumes any legal liability or responsibil'ity for the accuracy, completeness, or usefulness of any information, apparatus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…As shown in Figure 10, 1W catalysts (0.3 pbm K) have selectivities 50-200% higher than catalysts with nominal potassium loading (3.6-5.2 pbm K). Decreasing CH4 selectivity with increasing K loading is well documented in the literature [4,24,29].…”
Section: Selectivitymentioning
confidence: 57%
“…As shown in Figure 10, 1W catalysts (0.3 pbm K) have selectivities 50-200% higher than catalysts with nominal potassium loading (3.6-5.2 pbm K). Decreasing CH4 selectivity with increasing K loading is well documented in the literature [4,24,29].…”
Section: Selectivitymentioning
confidence: 57%
“…Both of these methods have been described in our previous DOE reports (e.g. Bukur et al, 1989b). Results from all wax (slurry) withdrawals are summarized in Table 3, whereas other major events during the run are listed in Table 4.…”
Section: Do I Imentioning
confidence: 99%
“…The preparation of precipitated Fe FT catalysts has been investigated previously by several academic research groups. Studies performed at Texas A&M University by Bukur et al span more than 10 years and resulted in the development of active, selective, and stable catalysts prepared by a continuous co-precipitation method to carefully control pH and temperature, which are among the most active iron catalysts reported in the literature. Studies showed that the addition of potassium (K) as a promoter to iron increases selectivity to olefins and heavy hydrocarbons, increases water–gas shift (WGS) activity, and can increase or decrease FTS activity, depending upon the amount of K used.…”
Section: Introductionmentioning
confidence: 99%